Seismicity analysis of the Southern Java region (2020-2024) based on the b-value and a-value using the maximum Likelihood method - Apriyanti, Syafrida Dwi; Fatmasari, Nurvita; Wijayanto, Mirda Prisma; Achmad, Arifin; Muflihatun (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2025)
This study investigates the seismicity analysis of the Southern Java region using earthquake data obtained from BMKG Banjarnegara, comprising 1064 events recorded between 2020 and 2024. The study area spans coordinate 7.5°S-8.5°S and 108.31°E-109.50°E. The analysis was conducted using Microsoft Excel, ZMAP 7.0, and QGIS 3.28.2 to calculate the a-value and b-value, key parameters that describe the frequency and magnitude distribution of earthquakes. The magnitude of 2.6 was the most frequently observed, with 150 recorded events, while earthquakes occurring at a depth of 10 km were the most common, totaling 210 events. The high density of seismic occurrences reflects significant tectonic activity in the region. Using the maximum likelihood method, the b-value was determined to be approximately 1.09 ± 0.04, and the a-value was calculated at 5.754. The relatively low b-value suggests areas of elevated stress, implying potential for larger-magnitude earthquakes. Additionally, the spatial distribution of the a-value highlights regions of heightened seismic activity. These findings contribute to a deeper understanding of seismic behavior in Southern Java and offer valuable insights to support disaster risk reduction and earthquake mitigation efforts in the region.